Base-Induced Cyclization of Active Methylene Isocyanides with Xanthate Esters: An Efficient Method for the Synthesis of 5-Alkoxy-4-(tosyl/ethoxycarbonyl)-1,3-thiazoles - Rajeev, Narasimhamurthy; Swaroop, Toreshettahally R.; Anil, Seegehalli M.; Bommegowda, Yadaganahalli K.; Rangappa, Kanchugarakoppal S.; Sadashiva, Marilinganadoddi P. (Synlett, 2017)
Sodium hydride-induced cyclization of 1-[(isocyanomethyl)sulfonyl]-4-methylbenzene or ethyl isocyanoacetate with various xanthate esters gave 5-alkoxy-4-tosylthiazoles or ethyl 5-alkoxythiazol-4-ylcarboxylates, respectively, in good to excellent yields. The xanthate ester S-methyl O-phenyl dithiocarbonate gave 5-(methylsulfanyl)-4-tosyl-1,3-thiazole when treated with 1-[(isocyanomethyl)sulfonyl]-4-methylbenzene under similar conditions.
Keywords: thiazoles; isocyanides; xanthate esters; cyclization